2004
DOI: 10.1074/jbc.m406317200
|View full text |Cite
|
Sign up to set email alerts
|

Omi/HtrA2 Promotes Cell Death by Binding and Degrading the Anti-apoptotic Protein ped/pea-15

Abstract: ped/pea-15 is a ubiquitously expressed 15-kDa protein featuring a broad anti-apoptotic function. In a yeast two-hybrid screen, the pro-apoptotic Omi/HtrA2 mitochondrial serine protease was identified as a specific interactor of the ped/pea-15 death effector domain. Omi/HtrA2 also bound recombinant ped/pea-15 in vitro and co-precipitated with ped/pea-15 in 293 and HeLa cell extracts. In these cells, the binding of Omi/ HtrA2 to ped/pea-15 was induced by UVC exposure and followed the mitochondrial release of Omi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 32 publications
2
66
1
Order By: Relevance
“…Protease activity of Omi is not necessarily required for cell death It has been reported that the protease activity of Omi, at least in part, contributes to cell death execution (Yang et al, 2003;Cilenti et al, 2004;Trencia et al, 2004). We found that WTS can promote the protease activity of Omi to induce cell death (Kuninaka et al, 2005).…”
Section: Proteolysis Of Warts By Omi Protease S Kuninaka Et Almentioning
confidence: 61%
See 1 more Smart Citation
“…Protease activity of Omi is not necessarily required for cell death It has been reported that the protease activity of Omi, at least in part, contributes to cell death execution (Yang et al, 2003;Cilenti et al, 2004;Trencia et al, 2004). We found that WTS can promote the protease activity of Omi to induce cell death (Kuninaka et al, 2005).…”
Section: Proteolysis Of Warts By Omi Protease S Kuninaka Et Almentioning
confidence: 61%
“…Based on those findings, Omi is being considered to act on maintenance of mitochondrial homeostasis. Collectively, protease activity is important for Omi to function properly in vivo, however, substrates reported to date are all involved in the apoptotic property of Omi (Yang et al, 2003;Cilenti et al, 2004;Trencia et al, 2004). Therefore, identification of non-apoptotic substrates of Omi is required to elucidate its physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the case of Pifithrin-a treatment, the forced expression of Bcl-2 in nucleostemin null ES cells to inhibit caspase-dependent apoptosis did not lead to even partial recovery of cell viability, implying that caspase-independent pathways also contributed significantly to the death of ES cells. A number of reports have described caspase-independent cell death, including induction by HtrA2/Omi [46] or apoptosis inducing factor [47]. However, it appears that the different types of caspaseindependent cell death do not share an underlying cause, except for the fact that the detrimental phenomena cannot be prevented by pharmacological or genetic inactivation of caspases [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this possibility, recent studies by Data are presented as the means ± SEM or %. Statistical significance was assessed by comparing all three groups of subjects our own as well as other laboratories have shown that PEA15 is highly regulated at the post-translational level [1,2,7,12]. Previous studies in cultured cells and in transgenic mice have shown that overexpression of the gene encoding PEA15 determines resistance to insulin action and impairs glucose-induced insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…It binds Fas-associated death domain (FADD) and caspase-8, thereby protecting against cytokine-induced apoptosis [9][10][11]. PEA15 also binds to Omi/HtrA2 to inhibit apoptosis triggered by stress and physical agents [12]. Importantly, there is evidence indicating that PEA15 anti-apoptotic action has an important role in the development and progression of certain cancers in humans as well as in rodents [13][14][15].…”
Section: Introductionmentioning
confidence: 99%